(untitled) (Veterinary Science, 2017)
A total of 352 birds (Gallus gallus domesticus), from different races were tested by means of the plate quick agglutination test (PQA) for the salmonelosis diagnosis. This procedure was carried out during the years 1989-92-93-94 and 98 in General Pico Agrarian Exhibition, La Pampa province, to allow their entrance.From the total 16 reacted positively.